INCREASING STUDENTS' DISASTER LITERACY THROUGH THE DISASTER MITIGATION CARD GAME (CAMIBEE) - Huda, Putriani Chayati; Rahmawati, Wulan; Khoeri, Ahmad Yusron; Nur Hayati, Muriani (Antis-publisher, 2024)
General background: Disaster literacy is crucial in equipping students with knowledge and preparedness for disaster risk reduction. Specific background: Previous educational approaches to disaster mitigation often lack engaging and interactive methods, which may reduce students' motivation to learn about disaster preparedness. Knowledge gap: Despite the significance of disaster education, there is a need for innovative approaches that effectively convey disaster mitigation concepts in a way that captivates students' interest. Aims: This community service program aims to enhance disaster literacy through the implementation of a disaster mitigation card game,